Identifikasi dan Hitung Koloni Bakteri pada Tangan Perawat Kamar Operasi Instalasi Bedah Sentral (IBS) RSUD Arifin Achmad Pekanbaru Sebelum dan Sesudah Cuci Tangan dengan Antiseptik Klorheksidin Glukonat - Devi Devi; Fauzia Andrini; Kuswan Ambar Pamungkas (Fakultas Kedokteran Universitas Riau, 2011)
Handwashing is an important thing to do and the most effective way in order to prevent nosocomial infection andinfection control. The most popular surgery’s handwashing is fuerbringer method. The purpose of this study was toknow the effectivity of hand washing from the nurses that work at central operation theather Arifin Achmad GeneralHospital Pekanbaru before and after washing hand with chlorhexidine gluconat antiseptic. This study method waslaboratoric descriptive with 22 samples which got from total sampling method. Bacterial was found from all sample.Bacterial which were found from the samples before hand washing were Coagulase negative staphylococci (CONS)(62.9%), Bacillus sp (20%), Metichillin resistant Staphylococcus aureus (MRSA) (11.4%) and Metichillin sensitiveStaphylococcus aureus (MSSA) (5.7%). Bacterial which found after doing hand wash were CONS (52.9%), Bacillussp (17.7%), Escherichia coli (8.8%), MRSA (11.8%), and MSSA (5.9%). The result of this bacterial colonizationarea showed the reduction of bacterial colonization after doing hand wash in 90.1% sample , which mostly reductionwas happen from II degree to I (36.4%).